Penyuluhan Tentang Deteksi Dini Kanker Dan Pemeriksaan Sadari - Wiwin Rohmawati; Endang Sawitri; Anna Uswatun Qoyyimah; Marwanti Marwanti (Universitas Muhammadiyah Klaten, 2024)
Cancer is the leading cause of death in the world, with cancer being the second leading cause of death in the world at 13% after cardiovascular disease. Experts estimate that 40% of cancers can be prevented by reducing risk factors for cancer. For this reason, efforts are needed to increase public awareness to prevent these risk factors and increase appropriate prevention and control programs. Therefore, it is important for women to carry out early detection of breast cancer which aims to detect cancer as early as possible so that it is easier to treat through Self Breast Examination or breast self-examination, often shortened to SADARI. Universitas Muhammadiyah Klaten plays a role in carrying out these activities as a form of community service activities. This service activity includes education regarding Early Detection of Breast Cancer and SADARI examination using leaflets and demonstrations.